2021
DOI: 10.1038/s43705-021-00040-0
|View full text |Cite
|
Sign up to set email alerts
|

Tree diversity and soil chemical properties drive the linkages between soil microbial community and ecosystem functioning

Abstract: Microbial respiration is critical for soil carbon balance and ecosystem functioning. Previous studies suggest that plant diversity influences soil microbial communities and their respiration. Yet, the linkages between tree diversity, microbial biomass, microbial diversity, and microbial functioning have rarely been explored. In this study, we measured two microbial functions (microbial physiological potential, and microbial respiration), together with microbial biomass, microbial taxonomic and functional profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 80 publications
5
37
2
Order By: Relevance
“…Individual tree species can affect the structure of the litter layer by influencing microclimatic conditions that drive soil microbial functions (Gottschall et al., 2019). Therefore, improved data on litter and root traits, in addition to their influence on soil quality and microclimate, are needed to improve our mechanistic understanding of the effects of tree identity on soil functions (Beugnon et al., 2021; Laliberté, 2017). Using belowground traits, rather than aboveground traits, is essential to predict soil functions, because different mechanisms are likely to operate belowground.…”
Section: Discussionmentioning
confidence: 99%
“…Individual tree species can affect the structure of the litter layer by influencing microclimatic conditions that drive soil microbial functions (Gottschall et al., 2019). Therefore, improved data on litter and root traits, in addition to their influence on soil quality and microclimate, are needed to improve our mechanistic understanding of the effects of tree identity on soil functions (Beugnon et al., 2021; Laliberté, 2017). Using belowground traits, rather than aboveground traits, is essential to predict soil functions, because different mechanisms are likely to operate belowground.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with our first hypothesis that soil microbial alpha diversity increases with the increasing tree species diversity, we found that plant community richness had a negative effect on soil bacterial diversity under the canopy of focal trees, indicating that the most diverse bacterial communities in our study occurred in monocultures and that diversity decreased with increasing community-level tree richness. This is in contrast with earlier work in grassland [10] and on fungal communities in the BEF-China experiment [26]. Unlike these earlier studies, we have collected soil samples underneath individual trees rather than at the community-level, and it is therefore reasonable to suggest that the decline in soil bacterial diversity may point to a ‘dilution effect’ [23, 76].…”
Section: Discussionmentioning
confidence: 72%
“…In forests, fungi are known to form symbiotic relationships with plants in forest soils [22][23][24] and fungal community composition is closely linked to tree diversity [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of identifying underlying mechanisms may arise from interrelated conceptual and methodological issues in the fields of microbial ecology and biogeochemistry. First, many litter decomposition studies de-emphasize the role of microbial composition in controlling soil carbon dynamics (e.g., Beugnon et al, 2021). This approach reflects the influential conceptual framework of hierarchical control of litter decomposition (e.g., Lavelle et al, 1993;Aerts, 1997).…”
Section: Introductionmentioning
confidence: 99%